Surface texture detection with artificial fingers - Mohamad Hanif, N. Hazrin H; Chappell, Paul H.; Cranny, Andy; White, Neil M. (IEEE, 2015)
This paper highlights the potential of using prosthetic devices to sense surface textures; an important characteristic of a lower arm that is often neglected. An artificial finger equipped with a piezoelectric sensor, mounted on a fingertip, has been designed to detect surface textures of different dimensions. Signal frequencies generated during the exploratory movement of the artificial finger reliably correlate to all the widths of grooves and ridges of the surface textures under investigation. This capability provides a positive outlook in recreating a touch sensation that has been previously lost from natural fingers and palms.